Karakteristik Pengajaran Ilmu Pengetahuan Sosial di Sekolah Menengah Pertama - Wuwuh Yunhadi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
A misleading conception of teaching-learning Sosial Sciences for elementary and secondary school in Indonesia has widely occurred. Social Science lesson is considered simple, from which learning is basically a recall and comprehension of a text, and the teaching model is simply providing students with textbook for reading. Similar to other lessons, the substance of IPS is obviously hard to teach. People change as well as the social life. Those changes are leading the changing of social science. Learning social science tries to understand those changing. The understanding of social science will help the learners, particularly young people, make reasonable decisions for public goods as citizens to live together and participate in social life.